2008
DOI: 10.4049/jimmunol.181.8.5360
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase Inhibition during Allergic Sensitization Increases STAT6-Independent Primary and Memory Th2 Responses

Abstract: Immune sensitization and memory generation are required for the development of allergic inflammation. Our previous studies demonstrate that the cyclooxygenase (COX) metabolic pathway is actively involved in allergic responses and COX inhibition increases allergic airway inflammation in a STAT6-independent fashion. To test the hypothesis that COX inhibition augments allergic inflammation by enhancing immune sensitization and memory, we sensitized STAT6 knockout mice with an i.p. injection of OVA with aluminum h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…1 Th2 cells, supporting a role for the COX pathway in regulating allergic inflammation (6)(7)(8)(9)(10)(11)(12)(13). Because COX inhibition increases allergic inflammation in humans and experimental animal models, this suggests that a COX product restrains allergen-induced inflammatory responses and may be a novel treatment strategy for allergic diseases.…”
mentioning
confidence: 99%
“…1 Th2 cells, supporting a role for the COX pathway in regulating allergic inflammation (6)(7)(8)(9)(10)(11)(12)(13). Because COX inhibition increases allergic inflammation in humans and experimental animal models, this suggests that a COX product restrains allergen-induced inflammatory responses and may be a novel treatment strategy for allergic diseases.…”
mentioning
confidence: 99%
“…13 Therefore, Treg cells may be a mechanism by which immune tolerance prevents the immune system from responding to innocuous environmental antigens. While we and others have reported that COX inhibition increased allergic airway inflammatory responses, 610 the effect of COX products and COX inhibition on allergen-induced immune tolerance in the airways is not known.…”
Section: Introductionmentioning
confidence: 85%
“…4 In addition, there was a higher prevalence of new-onset asthma in subjects who regularly used NSAIDs other than aspirin compared to nonusers. 5 In animal studies, COX inhibition with indomethacin increased allergic sensitization, allergen-specific immune memory response, and augmented allergic airway inflammation and Th2 immune responses, 610 supporting a role for the COX pathway in the development of allergic diseases. Similarly, mice deficient in COX enzymes have increased allergic inflammation compared to wild type (WT) mice.…”
Section: Introductionmentioning
confidence: 99%
“…STAT6 is activated by both IL-4 and IL-13 and plays an important role in Th2 cell differentiation and type 2 immune responses (1). We have previously shown that the cyclooxygenase (COX) inhibitor indomethacin augmented allergic Th2 cytokine responses and lung inflammation in a STAT6-independent manner (2, 3). However, which COX product(s) suppressed by COX inhibition is critical for indomethacin-induced STAT6-independent pro-allergic effect has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The COX pathway of arachidonic acid metabolism is responsible for the formation of PGD 2 , PGE 2 , PGF 2α , PGI 2 and thromboxane A 2 (TXA 2 ), and has immune regulatory functions in the development and manifestation of allergic diseases (2-11). COX-inhibiting drugs such as indomethacin and the COX-2 selective inhibitor NS-398 increased allergic inflammation in the airway and skin in mice (9, 12), suggesting that some lipid products formed in the COX pathway have inhibitory effects on allergic diseases.…”
Section: Introductionmentioning
confidence: 99%